Discourse Characteristics of Writing and Speaking Task Types on the TOEFL iBT® Test: A Lexico‐Grammatical Analysis. Issue 1 (June 2013) - Biber, Douglas; Gray, Bethany
Abstract: One of the major innovations of the TOEFL iBT ® test is the incorporation of integrated tasks complementing the independent tasks to which examinees respond. In addition, examinees must produce discourse in both modes (speech and writing). The validity argument for the TOEFL iBT includes the claim that examinees vary their discourse in accordance with these considerations as they become more proficient in their academic language skills (the explanation inference). To provide evidence in support of this warrant, we undertake a comprehensive lexico‐grammatical description of the discourse produced in response to integrated versus independent tasks, across the spoken and written modes, by test takers from different score levels. Discourse descriptions at several linguistic levels are provided, including vocabulary profiles, collocational patterns, the use of extended lexical bundles, distinctive lexico‐grammatical features, and a multidimensional (MD) analysis that describes the overall patterns of linguistic variation. In sum, we undertake a comprehensive linguistic analysis of the discourse of TOEFL iBT responses, interpreting observed linguistic patterns of variation relative to three parameters that are relevant in the TOEFL iBT context: mode, task type, and score level of test takers.